Connexins and Nitric Oxide Inside and Outside Mitochondria: Significance for Cardiac Protection and Adaptation - Shvedova, Maria; Anfinogenova, Yana; Popov, Sergey V.; Atochin, Dmitriy N. (Frontiers in Physiology, 2018)
Irreversible myocardial damage happens in the presence of prolonged and severe ischemia. Several phenomena protect the heart against myocardial infarction and other adverse outcomes of ischemia and reperfusion (IR), namely: hibernation related to stunned myocardium, ischemic preconditioning (IPC), ischemic postconditioning, and their pharmacological surrogates. Ischemic preconditioning consists in the induction of a brief IR to reduce damage of the tissue caused by prolonged and severe ischemia. Nitric oxide (NO) signaling plays an essential role in IPC. Nitric oxide-sensitive guanylate cyclase/cyclic guanosine-3',5'-monophosphate (cGMP)-dependent protein kinase type I-signaling pathway protects against the IR injury during myocardial infarction. Mitochondrial ATP-sensitive and Ca2+-activated K+ channels are involved in NO-mediated signaling in IPC. Independently of the cGMP-mediated induction of NO production, S-nitrosation represents a regulatory molecular mechanism similar to phosphorylation and is essential for IPC. Unlike conditioning phenomena, the mechanistic basis of myocardial stunning and hibernation remains poorly understood. In this review article, we hypothesize for the first time that the disruption of electrical syncytium of the myocardium may be the key process underlying myocardial stunning and hibernation. Considering that the connexins are the building blocks of gap junctions which represent primary structural basis of electrical syncytium, we discuss data on the involvement of connexins into myocardial stunning and hibernation as well as into conditioning. We also show how NO-mediated signaling is involved in myocardial stunning and hibernation. Connexins represent an essential element of adaptation phenomena of the heart at the level of both the cardiomyocytes and the mitochondria. Nitric oxide targets mitochondrial connexins which may affect electrical syncytium continuum in the heart. Mitochondrial connexins may play an essential role in NO-dependent mechanisms of myocardial adaptation to ischemia.